Penerapan Model Pembelajaran Numbered Head Together - Bobby Giridson Rihileo (Journal of Character and ELementary Education, 2026)
Abstract: This study was motivated by the low learning outcomes of fourth-grade students in Mathematics, particularly in the topic of multiplication of whole numbers at SD Negeri Naikoten 2. Students tended to be passive during lessons, had limited participation in discussions, and found it difficult to understand multiplication concepts. Therefore, this research aimed to improve students’ learning outcomes through the implementation of the Numbered Head Together (NHT) cooperative learning model assisted by a multiplication snake-and-ladder media. This research employed a Classroom Action Research (CAR) design, which consisted of two cycles, each including four stages: planning, implementation, observation, and reflection. The subjects were 20 students of grade IV at SD Negeri Naikoten 2, during the first semester of the 2025/2026 academic year. Data were collected through observation of teacher and student activities, as well as written tests conducted at the end of each cycle. The data were analyzed using descriptive qualitative and quantitative methods by comparing results between cycles. The findings revealed a significant improvement in teacher performance, student engagement, and learning outcomes. Teacher activity increased from an average score of 50 (observer I) and 60 (observer II) in the first cycle to 95 and 90 in the second cycle, categorized as very good. Student activity also improved from an average of 65 (observer I) and 55 (observer II) in the first cycle to 90 and 85 in the second cycle, also categorized as very good. Furthermore, the average learning outcome score increased from 51.8 in the first cycle to 77.7 in the second cycle, and the percentage of students achieving mastery rose from 35% to 80%, indicating that 16 out of 20 students met the Minimum Mastery Criteria (MMC). In conclusion, the implementation of the Numbered Head Together learning model assisted by the snake-and-ladder media effectively enhanced students’ learning outcomes on the topic of multiplication of whole numbers. The model fostered an active, enjoyable, and collaborative learning environment that increased students’ motivation and understanding of mathematical concepts. Keywords: Numbered Head Together, learning outcomes, multiplication of whole numbers, Classroom Action Research.